HIBRIDITAS TOKOH DALAM NOVEL REMAJA KERONCONG CINTA KARYA AHMAD FAISHAL - Dheny Jatmiko (JENTERA: Jurnal Kajian Sastra, 2015)
The novel Keroncong Cinta by Ahmad Faishal was an adolescent novel about social, politics and culture life of a family due to the interracial Europe-Java marriage at the end of colonial era. This research used postcolonial approach to reveal the forms of characters hybridity and interpret it in relation to the colonial era in Dutch East Indies context. This research discovered that the hybridity in Dutch East Indies caused by marriage, concubinage, education and the spirit to gain equality experienced by the Indo. The forms of characters hybridity showed through the identity ambivalence and ambiguity as the results of contradiction between indigenous and Europe cultures. These forms among others are identity ambiguity and awareness of the Indo as the third class, the blurring of colonialism contradictive lines and a lady’s Europe orientation. This research also proofed that adolescent literatures, as a part of popular literatures, are not only literatures filled with entertainment and simplicity.AbstrakNovel Keroncong Cinta karya Ahmad Faishal merupakan novel remaja yang menceritakan kehidupan sosial, politik, dan budaya sebuah keluarga karena perkawinan antarras Eropa-Jawa di akhir masa kolonial. Penelitian ini memanfaatkan pendekatan poskolonial untuk mengungkap bentuk-bentuk hibriditas tokoh dan diinterpretasi dalam kaitannya dengan konteks masa kolonial di Hindia Belanda. Penelitian ini menemukan bahwa hibriditas di Hindia Belanda disebabkan oleh perkawinan, pergundikan, pendidikan, dan semangat memperoleh persamaan derajat yang dialami kalangan Indo. Bentuk-bentuk hibriditas tokoh ditunjukkan dengan adanya ambivalensi dan ambiguitas identitas sebagai akibat dari kontradiksi antara kultur Eropa dan pribumi. Bentukbentuk hibriditas tokoh antara lain ambiguitas identitas dan kesadaran orang Indo sebagai kelas ketiga;pengaburan garis-garis kontradiktif koloniaslisme; dan orientasi ke-Eropa-an seorang Nyai. Penelitian ini sekaligusmembuktikan bahwa sastra remaja, sebagai bagian sastra populer, bukan hanya sastra yang berisi hiburan dan kesederhanaan.